Effective Cross-cultural Advertising: Moderating Roles of Ethnic Identity and Religiosity in Pitching Controversial Vs. Non-controversial Products to Diasporic Communities. Issue 1 (2nd January 2022) - Asim, Mian; Rasul, Azmat; Shin, Donghee
ABSTRACT: This study evaluates the impact of casting ethnically identical actors in advertisements to elicit a favourable attitude towards the advertisement and the product. Our study explores the effectiveness of cross-cultural advertising and investigates the effectiveness of advertisements. In this experimental study, a national sample (N = 252) was recruited with an equal number of Indian and Middle Eastern subjects, which were randomly chosen across the United States. The results reflect that attitude formation patterns for Indians and Middle Easterners are dissimilar when they are exposed to advertisements containing actors with varied ethnicities